Prevalence of different dairy cattle diseases in selected dairy areas and farms of Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2018)
The present study was designed to have a comprehensive epidemiological data of the circulating diseases in Pubna cattle in Pubna and sirajgonj districts of Bangladesh. Two sites were selected for the study as the Nucleus Breeding Hard (NBH); which is located in the BLRI-RS, Baghabari, Sahjadpur, Siragjang and the community; consists of three villages of Bera upazila of Pabna district namely Khar-bagan, Hatail-aralia and Char-sabolla. The total cattle population was 576 (506 in the community and 70 in the NBH). The overall weather was hot and humid. A total of 965 clinical cases of cattle of different age and sex were diagnosed during the period from July, 2017 to June, 2018.The descriptive statistics suggested that endo-parasites (15.67%), FMD (27.51%), non-specific diarrhea (7.73%) and post-partum anoestrus (7.78%) are the most prevailing diseases in the community and endo-parasites (21.82%), foot-rot (15.15%), non-specific fever (7.27%), dermatochalasis (5.45%) and conjunctivitis (4.85%) are the most prevailing diseases in the NBH. Population data shows that there was an endemic outbreak of FMD in the community between March to May 2018 where almost 50% cattle were affected by the disease though calf morbidity was low (2.69%) but all the affected calf died. Non-specific diarrhea was more common in older individuals (14% in over 3years old cattle) mostly in cows (14.2%) and occurred in summer (9.84%) and winter (8.81%) may be because of the ignorance of the farmers to supply clean water to their animals. Although, we routinely de-worm our cows in the community and in the NBH round the year we found many cases of parasitic gastro-enteritis in both the locations which suggested that our de-worming practice is not working. Repeated study of the same kind can provide us a large set of data on cattle disease prevailing in the area which may provides valuable insight to design and implement priority based research on specific disease and to take efficient control strategies against that disease.Asian Australas. J. Biosci. Biotechnol. 2018, 3 (3), 231-236